Studies on flue gas desulfurization using EDA/SiO2–phosphoric acid solution as an absorbent. Issue 126 (10th December 2015) - Bo, Wen; Zhang, Junjie; Li, Hongxia; Song, Xiangjia
Abstract : The synthesis route of EDA/SiO2, with the additive of H3 PO4 . It can be used as an absorber to absorb SO2 in flue gas. Abstract : Flue gas desulfurization by immobilized amines is a new desulfurization technique. EDA/SiO2 and an H3 PO4 additive were used as an absorbent for desulfurization. SO2 was absorbed by the system and desorbed from the loaded solution. And the cycling operation was also analyzed in the experiments. Some technological conditions such as the amount of EDA/SiO2, the temperature, concentration of SO2 and pH value were experimentally researched. With the optimized process, the absorption efficiency of this system could reach 98% and the desorption efficiency was over 50%, showing good absorption/desorption capability and promising potential to be applied in desulfurization.